Revisiting Okun's Relationship - Robert Dixon; Guay C. Lim; Jan C. van Ours (Institute for the Study of Labor (IZA), 2016)
Our paper revisits Okun's relationship between observed unemployment rates and output gaps. We include in the relationship the effect of labour market institutions as well as age and gender effects. Our empirical analysis is based on 20 OECD countries over the period 1985-2013. We find that the share of temporary workers (which includes a high and rising share of young workers) played a crucial role in explaining changes in the Okun coefficient (the impact of the output gap on the unemployment rate) over time. The Okun coefficient is not only different for young, prime-age and older workers, it decreases with age. From a policy perspective, it follows that an increase in economic growth will not only have the desired outcome of reducing the overall unemployment rate, it will also have the distributional effect of lowering youth unemployment.
Keywords: J64; 330; Okun's law; unemployment; equilibrium unemployment rates